AN ECONOMIC ANALYSIS TO ESTIMATE PROFIT FUNCTION AND MEASUREMENT TECNICAL EFFICIENCY FOR PRODUCTION POULIRT IN DIYALA PROVINCE - Zaidan, Ali G.; Ali, Eskander H.; Khater, Sadoon F.; Mahmood, Mhanaa A. (Diyala Agricultural Sciences Journal, 2016)
The reseach aims to study most important factors those affecting Profit function and estimate stochastic production function to measure technical efficiency . The study used cross-section data from random sample consist of 64 poultry farmers from Diayla Province.The results showed description analysis of production costs from ,that variable and fixed costs consist about 88.78% and 11.12% from total costs respectivty. The results of quantitative analysis of Profit function showed that price of product was the most important factor that affecting in profit when compared with other varaibles of product quantity and cost average .The study used stochastic border approch to estimate super production function which have two independent varaibles (Labour and Capital ) ,and the analysis aproved by using (ML) Maximum Liklihood their compatible with economic logic .Labour was most affecting on Polutary production,while technical efficiency average was 0.98 .when studying the relation between size of project and technical efficiency and profit we found that the optimal capacity was 50.5 -100.5 thousand bird because it achived efficiency about 0.99 and profit about 897.06 Dinar/Kg .The study proved the hypothesis that said (The Miximize Outpout is not always Miximize Profit).